Preoperative alcohol consumption, intraoperative bleeding and postsurgical pain may increase the risk of postoperative delirium in patients undergoing radical retropubic prostatectomy - Lađević Nikola; Knežević Nebojša Nick; Magdelinić Anđela; Likić-Lađević Ivana; Durutović Otaš; Stamenković Dušica; Jovanović Vesna; Lađević Nebojša (Vojnosanitetski Pregled)
Background/Aim. The incidence of postoperative delirium (POD) after non-cardiac surgery is a problem not often recognized by many anesthesiologists. The objective of our study was to detect POD and its possible cause, in patients undergoing radical retropubic prostatectomy (RRP) under general anesthesia. Methods. After Ethical Committee approval, we enrolled 80 patients, ASA (the American Society of Anestesiology) status II, scheduled to undergo RRP un-der general anesthesia, in a prospective study. All patients completed MMSE tests (the Folstein Mini Mental State Ex-am) the evening before, and 48 hours after the surgery. Assessment for the presence and severity of delirium was per-formed using CAM (the Confusion Assessment Method), and an assessment of the degree of agitation and sedation using RASS (the Richmond Agitation and Sedation Scale). Results. The average preoperative MMSE score (28.59 ± 1.04) significantly decreased following the surgery (27.74 ± 1.52) (p < 0.0001). The average postoperative MMSE score trend descended in correlation to intraoperative bleeding (p = 0.036). The patients with higher pain scores had significant decline in MMSE after the surgery (28.75 vs. 26.25; p < 0.001). Five patients were considered positive for delirium, and four of them reported regular alcoholic drinks intake (> 1 drink per day) preoperatively (p < 0.0001). Based on RASS score, 13 patients (16.3%) were agitated or sedated, and they had statistically significantly higher intraoperative bleeding (p < 0.001). Conclusion. Results of this study emphasize the importance of proper preoperative evaluation; especially regarding the alcohol consumption since all the patients that developed POD reported moderate alcohol consumption. Further-more, greater intraoperative bleeding and postoperative pain scores did not influence the occurrence of delirium, but resulted in lower postoperative MMSE scores, which high-lights the importance of adequate intraoperative treatment of patients during surgery and anesthesia in order to reduce the risk of developing POD.